2020
DOI: 10.1002/aisy.202000146
|View full text |Cite
|
Sign up to set email alerts
|

Reprogrammable Untethered Actuator for Soft Bio‐Inspired Robots

Abstract: The use of active materials for the actuators in soft robots allows for safe interactions and adaptable locomotion. However, stimulating the behavior of soft robots as well as reprogramming them and implementing reversible control in them remains a challenge. Herein, a method for fabricating soft, bio‐inspired, untethered, infrared‐driven actuators that exhibit reversible and reprogrammable behaviors is proposed. By exploiting the mismatch in the infrared‐driven thermomechanical responses of the two active mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…S7 †), we conducted biocompatibility tests which demonstrated that the hydrogel robot has good biocompatibility. Compared to previous work, 62 this paper presents advancements in the manufacturing technology of soft robots, enabling the reversible and programmable functionality of a single-layer hydrogel robot. Besides, if combined with flexible sensing, 63 multi-physical cooperative driving, 64,65 and therapeutic capabilities, 66,67 the single-layer hydrogel robot could realize the integration of diagnosis and treatment and environmental monitoring in the biomedical field.…”
Section: Response Principle Of the Single-layer Hydrogel Robotmentioning
confidence: 99%
“…S7 †), we conducted biocompatibility tests which demonstrated that the hydrogel robot has good biocompatibility. Compared to previous work, 62 this paper presents advancements in the manufacturing technology of soft robots, enabling the reversible and programmable functionality of a single-layer hydrogel robot. Besides, if combined with flexible sensing, 63 multi-physical cooperative driving, 64,65 and therapeutic capabilities, 66,67 the single-layer hydrogel robot could realize the integration of diagnosis and treatment and environmental monitoring in the biomedical field.…”
Section: Response Principle Of the Single-layer Hydrogel Robotmentioning
confidence: 99%
“…This material and the optical mechanism are also potential prospects for flagellated and ciliary soft robots. Another infrared-actuated bilayer robot was developed by Yang et al [92]. They used polylactic acid and carbon nanotubes as the infrared-responsive layer, and polyethylene terephthalate was used as a transparent layer.…”
Section: Optical Microrobotsmentioning
confidence: 99%
“…Over the past decade, substantial efforts have been made in the development of soft robots, which exhibit conformable complex motions that ensure safe interactions between humans and robots. [1][2][3][4] By employing various actuation methods, [5][6][7][8][9][10][11] soft robots are able to perform a variety of bioinspired deformations, [4,[12][13][14] ranging from bending, [15][16][17][18] contraction, [19][20][21] to elongation. [22][23][24] However, despite these advances, rotation remains a persistent challenge in soft robots.…”
Section: Introductionmentioning
confidence: 99%